-(9q+7)+3(2q-5)=

Simple and best practice solution for -(9q+7)+3(2q-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(9q+7)+3(2q-5)= equation:


Simplifying
-1(9q + 7) + 3(2q + -5) = 0

Reorder the terms:
-1(7 + 9q) + 3(2q + -5) = 0
(7 * -1 + 9q * -1) + 3(2q + -5) = 0
(-7 + -9q) + 3(2q + -5) = 0

Reorder the terms:
-7 + -9q + 3(-5 + 2q) = 0
-7 + -9q + (-5 * 3 + 2q * 3) = 0
-7 + -9q + (-15 + 6q) = 0

Reorder the terms:
-7 + -15 + -9q + 6q = 0

Combine like terms: -7 + -15 = -22
-22 + -9q + 6q = 0

Combine like terms: -9q + 6q = -3q
-22 + -3q = 0

Solving
-22 + -3q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + -3q = 0 + 22

Combine like terms: -22 + 22 = 0
0 + -3q = 0 + 22
-3q = 0 + 22

Combine like terms: 0 + 22 = 22
-3q = 22

Divide each side by '-3'.
q = -7.333333333

Simplifying
q = -7.333333333

See similar equations:

| 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= | | y=6x+18 | | -510=-4+2x | | 11x+8=69 | | 2x+4x-8=34 | | 8y+10=16-8y | | 10x-7=3x+5 | | 15-5(3-8y)= | | -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) |

Equations solver categories